1996
DOI: 10.1016/0014-5793(96)01012-5
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of xylitol in the mammalian lens is related to glucuronate metabolism

Abstract: Cataract remains the major cause of blindness worldwide and a common complication of diabetes. Polyol Preparation of lens lysates accumulation in the lens is associated with cataract formation.Freshly dissected bovine or rat lenses were homgenised in 2 ml of a Here we present evidence for a novel pathway for xylitol suitable ice-chilled assay buffer, using a manual Braun Homogeniser. production in the lens involving glucuronate metabolism. Xylitol Membranes and cell debris were removed by brief centrifugation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…MIOX, ALR1, gulonate dehydrogenase, xylulose reductase, and xylulose kinase) could be demonstrated in kidney tissues (Fig. 2D), which confirmed the existence of a G-X pathway in the kidney cortical tubules, as it has been described in the eye lens previously and is akin to the polyol pathway (25)(26)(27)(28).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…MIOX, ALR1, gulonate dehydrogenase, xylulose reductase, and xylulose kinase) could be demonstrated in kidney tissues (Fig. 2D), which confirmed the existence of a G-X pathway in the kidney cortical tubules, as it has been described in the eye lens previously and is akin to the polyol pathway (25)(26)(27)(28).…”
Section: Resultssupporting
confidence: 63%
“…Following another phenol-chloroform extraction, the RNA was reprecipitated with ethanol. About 2 g of total RNA was subjected to the first strand cDNA synthesis using Moloney murine leukemia virus-RT and oligo(dT) 25 as a primer. The cDNA was suspended in 250 l of 10 mM Tris-EDTA buffer, pH 7.4, and kept at Ϫ70°C until further use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be no reason to doubt that the xylitol detected in the lenses comes from xylose in the medium, although Hayman et al (1966) reported the presence of enzymes in rabbit lenses capable of synthesizing xylulose from glucuronate, and Goode, Lewis and Crabbe (1996) speculated that this pathway was responsible for lenticular production of xylitol from glucose (via myoinositol, glucuronate, gulonate, keto-gulonate, and xylulose, which could be converted to xylitol by SDH). However, no measurable xylitol was found in the lenses incubated without xylose, even in the presence of high concentrations of glucose or other sugars.…”
Section: Discussionmentioning
confidence: 94%
“…The enzyme is highly expressed in liver and kidney of the human and has been shown to be localized in the brush-border membranes of proximal tubular cells of the mouse kidney, suggesting a role for the enzyme in water reabsorption and cellular osmoregulation by producing xylitol [3]. Moreover, enzymes of the glucuronic acid pathway are present in mammalian lens, and the flux of sugars and xylitol through this pathway has been suggested to be involved in the osmoregulation process of the lens and the etiology of sugar cataracts [4]. In apoptosis of human T lymphoma cells induced by 9,10-phenanthrenequinone, a major component in diesel exhaust particles, XR is upregulated and deteriorates the apoptotic signaling through the generation of reactive oxygen species [5].…”
mentioning
confidence: 99%